Exposure to perfluoroalkyl substances and allergic outcomes in children: A systematic review and meta-analysis - Luo, Yuehua; Deji, Zhuoma; Huang, Zhenzhen (Environmental research, 2020)
Perfluoroalkyl substances (PFASs) are persistent organic pollutants and widespread throughout the environment. Although exposure to PFASs may contribute to the development of allergic diseases in children, evidence about this association remains inconclusive. To conduct a systematic review and meta-analysis to assess the association between PFASs exposure and allergic diseases in children based on current evidence. The databases including PubMed, EMBASE, and Web of Science were searched to identify all observational studies that examined the association between PFASs exposure and the risk of childhood allergic diseases. The Newcastle-Ottawa Scale was used to evaluate the quality of case-crossover studies, and a previously validated quality assessment framework was used for observational studies lacking control groups. Random-effects meta-analysis models were applied to pool odds ratio (OR) with 95% confidence intervals (CIs). From an initial 94 articles (after duplicate removal), 13 studies through full-text assessment were included for quantitative assessment and descriptive synthesis. They are ten cohort studies, two cross-sectional studies, and one case-control study. The pooled estimates showed that perfluorononanoic acid (PFNA) was associated with eczema (OR = 0.89, 95% CI = 0.80–0.99), perfluorooctanesulfonic acid (PFOS) with atopic dermatitis (OR = 1.26, 95% CI = 1.01–1.58), and perfluorooctanoic acid (PFOA) with allergic rhinitis (OR = 1.33, 95% CI = 1.13–1.56). However, no such significant associations were found for wheeze and asthma. The meta-analysis results suggest that PFASs exposure could potentially be associated with eczema, atopic dermatitis, and allergic rhinitis during childhood, but not with childhood asthma or wheeze. Future studies are needed to verify these findings. •Meta-analysis for relationship between PFASs exposure and childhood allergic outcomes.•Exposure to PFASs associated with eczema, allergic rhinitis and atopic dermatitis.•No significant associations between PFASs and asthma and wheeze.